Factors influencing the flexibility of fertility theories - Slimani, Fatma Zohra; Slimi, Fatma Zohra (The International tax journal, 2025)
Fertility ideas, especially ones tied to how populations shift over time, try to make sense of birthrate changes in different places and eras. Still, their usefulness shifts depending on economic, cultural, or system-based settings. Here’s a look at what shapes how stretchable - or adjustable - these fertility concepts really are, pulling from studies in both Western and Arab regions. The point? Forces like social structure, beliefs, and organizational setups together shape whether such models hold up where they’re used.